Spatial Distribution of COVID-19 Vulnerable Areas in Tambora District, Jakarta Barat - Yansen; Mangapul P. Tambunan; Rudy P. Tambunan (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2021)
The COVID-19 pandemic has spread in almost all countries and has caused many casualties. Jakarta is one of the areas with the highest number of COVID-19 sufferers in Indonesia. The purpose of this study was to analyze the distribution of areas vulnerable to the COVID-19 pandemic in Tambora District, Jakarta Barat. The variables used are demographic, socio-economic, health, and physical characteristics. The distribution of COVID-19 sufferers in Tambora District since the beginning of the pandemic has been detected in 7 sub-districts out of 11 sub-district. The highest number of COVID-19 sufferers in November 2020 were in the west, southwest and southeast side, while the least number of sufferers was in the south and northeast side. Jembatan Besi and Roa Malaka sub-districts showed contrasting conditions compared to their surrounding areas because those were the areas with the most and the least number of COVID-19 sufferers. The results showed that the areas with a very high level of vulnerability to COVID-19 are located in the west, southwest, central, north, and southeast side of Tambora District. Furthermore, areas with a high level of vulnerability are located in the north, center, and south. Then, the areas with a moderate level of vulnerability are located on the south and east sides, while the areas with a low level of vulnerability are located on the northeast side.